INTERNALISASI NILAI-NILAI ISLAM RAHMATAN LIL ALAMIN PADA PEMBELAJARAN AL ISLAM DAN KEMUHAMMADIYAH (AIK/ISMUBA) DI SEKOLAH MENENGAH ATAS MUHAMMADIYAH DAERAH MINORITAS - Muhammad Tamrin (TA'LIM : Jurnal Studi Pendidikan Islam, 2020)
Teaching Islam, Kemuhammmadiyahan and Arabic was a compulsory subject that should be taught at elementary and secondary level students. At Muhammadiyah educational institution, Ismuba was arranged and continuously improved for introducing Islam and Muhammadiyah. For Muslim students, Ismuba was taught the value of Islam to be comprehended, experienced, and practiced as the way of life, both personal and community life. While for non-Muslim students, teaching Islam, Kemuhammmadiyahan and Arabic was to introduce Islam and the universal values ​​which is a mercy for the universe and also to introduce Muhammadiyah organizations. The study was done in two locations. The first location was Muhammadiyah Ende High School which is the majority was Catholic and second location was Waengapu Muhammadiyah High School, East Sumba District which is the majority was Protestant. This study aimed at identifying the internalization pattern of Islam Rahmatan Lil Alamin in AIK / Ismuba Learning. In this field research, the descriptive qualitative methods was used. The data was obtained through interview, observation, and documentation. While the data was analyzed using Milles and Huberman model’s interactive data analysis technique.